Features of program implementation of CRC32 check sum computation on the example of PKZIP, WINZIP, ETHERNET; Modern technique and technologies MTT' 2012 - Mytsko E. A. Evgeniy Aleksandrovich (Section VII: Informatics and Control in Engineering Systems, 2012)
Заглавие с титульного листа